2020
DOI: 10.1093/jee/toaa120
|View full text |Cite
|
Sign up to set email alerts
|

Energy Reserve Compensating for Trade-Off Between Metabolic Resistance and Life History Traits in the Brown Planthopper (Hemiptera: Delphacidae)

Abstract: Development of insecticide resistance often changes life history traits of insect pests, because metabolic detoxification of insecticides in insect bodies requires huge energetic reserves. The brown planthopper, Nilaparvata lugens (Stål), an important insect pest of rice crop in East and Southeast Asia, has developed strong resistance to imidacloprid from mid-2000s. The aim of this study was to examine the costs of life history traits and reveal changes in energy reserves with developing imidacloprid resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Imidacloprid‐resistant strains were collected in 2009 (VN09‐1 and VN09‐3) and 2010 (VN10‐1) in Vietnam and 2014 in the Kumamoto prefecture, Japan (KR‐14). VN09‐3_F 24 was the most resistant laboratory‐selected strain established from VN09‐3 with exposure to imidacloprid for 24 generations 20–22 . Izumo‐87♀ x VN09‐1♂_F 1 (IxV‐F 1 ) and Izumo‐87♂ x VN09‐1♀_F 1 (VxI‐F 1 ) were F 1 s of the VN09‐1 and Izumo‐87 strains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidacloprid‐resistant strains were collected in 2009 (VN09‐1 and VN09‐3) and 2010 (VN10‐1) in Vietnam and 2014 in the Kumamoto prefecture, Japan (KR‐14). VN09‐3_F 24 was the most resistant laboratory‐selected strain established from VN09‐3 with exposure to imidacloprid for 24 generations 20–22 . Izumo‐87♀ x VN09‐1♂_F 1 (IxV‐F 1 ) and Izumo‐87♂ x VN09‐1♀_F 1 (VxI‐F 1 ) were F 1 s of the VN09‐1 and Izumo‐87 strains.…”
Section: Methodsmentioning
confidence: 99%
“…VN09-3_F 24 was the most resistant laboratory-selected strain established from VN09-3 with exposure to imidacloprid for 24 generations. [20][21][22] Izumo-87♀ x VN09-1♂_F 1 (IxV-F 1 ) and Izumo-87♂ x VN09-1♀_F 1 (VxI-F 1 ) were F 1 s of the VN09-1 and Izumo-87 strains. All insects were reared on rice seedlings in a glass bottle (6.5 cm diameter, 18 cm height) covered with a cloth mesh at 26°C under a long-day photoperiod (16L:8D) without exposure to insecticides.…”
Section: Insectsmentioning
confidence: 99%
“…For instance, male insects are usually smaller and play different adaptive roles than females (Field et al, 2015;Stillwell et al, 2010). Thus, it is reasonable to expect that sex-dependent physiological responses would shape the adaptive success of insects facing insecticidal challenges (Andreazza et al, 2020;Cremonez et al, 2019;Feng et al, 2019;Fujii et al, 2020;Haddi et al, 2016Haddi et al, , 2017. Here, although the continuous selection for PBO-synergized imidacloprid resistance led to providing both E. heros males and females with increased respiratory activities, previous investigations have shown that only E. heros males exhibited reduced respiratory activities when sublethally exposed to imidacloprid (Haddi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Population parameters include the average generation period ( T ), intrinsic growth rate ( rm ), net reproduction rate ( R 0 ), and weekly growth rate ( λ ). The relative fitness was calculated based on the relative fitness ( R f ) = R 0 / R 0 of the control group ( Fujii et al, 2020 ; Zhang et al, 2018 ). The age-stage-specific survival rate ( S xj ), age-specific survival rate ( l x ), female age-specific fecundity ( f x ), age-specific fecundity ( m x ), and age-specific maternity ( l x m x ) were plotted using GraphPad Prism 9.…”
Section: Methodsmentioning
confidence: 99%